2016
DOI: 10.1063/1.4951002
|View full text |Cite
|
Sign up to set email alerts
|

Microwave absorption performance enhanced by high-crystalline graphene and BaFe12O19 nanocomposites

Abstract: The nanocomposites, consisting of BaFe12O19 ferrite and few-layer graphene sheets (FL-GSs) in various weight ratios (1−9 wt. %), were fabricated by a mechanical mixing method. The high-crystalline FL-GSs were prepared by direct current arc discharge evaporation of pure graphite electrodes in an H2–Ar gas mixture. We measured the electromagnetic properties, including effective magnetic permeability and effective permittivity in addition to microwave absorption performance, of the FL-GSs/BaFe12O19 nanocomposites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Graphene (GR) exhibits two-dimensional (2D) sp 2 -hybridized honeycomb structure, large surface area, and high electron mobility, , so it is often used as an additive to improve dielectric properties of composites. For instance, Bansala et al prepared GR-based polyurethane nanocomposites with enhanced electrical conductivity and superior electromagnetic interference (EMI) shielding effectiveness (SE) in the Ku band frequency region.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene (GR) exhibits two-dimensional (2D) sp 2 -hybridized honeycomb structure, large surface area, and high electron mobility, , so it is often used as an additive to improve dielectric properties of composites. For instance, Bansala et al prepared GR-based polyurethane nanocomposites with enhanced electrical conductivity and superior electromagnetic interference (EMI) shielding effectiveness (SE) in the Ku band frequency region.…”
Section: Introductionmentioning
confidence: 99%
“…The imaginary part of permittivity provides information about energy dissipation. In the ε″ curves, the resonance peaks can be attributed to the leakage conductance and lags in polarization [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is well concluded that the permeability of absorber is associated with hysteresis loss, eddy current effect, domain-wall resonance, natural ferromagnetic resonance, and exchange resonance [34][35][36][37] . In the case of the weak applied microwave field, the hysteresis loss can be neglected.…”
Section: Resultsmentioning
confidence: 99%